Carbachol-Induced Secretion and Homologous Desensitization in Rat Basophilic Leukemia (RBL-2H3) Cells Transfected With Human m2 Muscarinic Acetylcholine Receptors - Kazuhiko Oishi; Akihiro Sakurai; Noriyasu Seki; Tomokazu Yoshizumi; Masaatsu K. Uchida (Elsevier, 2004)
Carbachol (CCh) caused a dose-dependent release of β-hexosaminidase and an increase in the production of inositol 1,4,5-trisphosphate (IP3) in RBL-2H3 cells transfected with m2 mAChR cDNA (RBL-m2 cells). The secretion was completely inhibited by LaCl3 and pertussis toxin. The secretion was dependent on extracellular Ca2+ and mediated through the pertussis toxin-sensitive G protein. Exposing RBL-m2 cells to 100 μM CCh for 30 min in Ca2+-free medium (desensitizing treatment) inhibited the secretion induced by the subsequent addition of 10 μM CCh plus Ca2+, but not by stimulating the high affinity IgE receptor (FcεRI). Desensitizing treatment of RBL-m2 cells reduced the affinity of the lipophilic ligand [3H]quinuclidinyl benzilate to m2 mAChR without a reduction of the total m2 mAChR number. The treatment also decreased the cell surface mAChR number to 14% with a slight reduction in its affinity. Desensitizing treatment of RBL-m2 cells inhibited the CCh-induced transient increase in levels of IP3 and intracellular Ca2+ concentration. The results suggested that the CCh-induced desensitization of m2 mAChR-mediated secretion is due to the receptor sequestration followed by blocking the increase in [Ca2+]i and that this desensitizing mechanism is receptor-subtype-specific. Keywords:: m2 muscarinic receptor, desensitization, secretion, RBL-2H3 cell, transfection